The moderating effects of job demand between job resources, work-life enrichment, and core self-evaluations on work engagement among academics in Malaysian public universities - Ng, Lee Peng (2015)
The purpose of this research is to examine the relationship between job resources (i.e. perceived organisational support, immediate superior support, colleague support, autonomy, recognition, job prestige, and perceived external prestige), work-life enrichment and core self-evaluations on work engagement among academics in Malaysian public universities. In addition, this study also examined the moderating effects of job demands on these relationships. The survey questionnaire was designed to elicit responses from the participants. A total of 756 questionnaires were distributed to the academics from 18 public universities in Peninsular Malaysia. Three hundred eighty five (385) usable questionnaires were returned, yielding a response rate of 50.9%. The data were analysed using multiple regression analysis. The results indicated that immediate superior support, perceived external prestige, work-to-personal life enrichment, personal life-to-work enrichment, and core self-evaluations were positively related to work engagement. On the other hand, colleague support was found to be negatively related to work engagement. Result from hierarchical regression analysis showed that job demands only moderate the relationship between work-to-personal life enrichment and work engagement. This means the effect of work- to-personal life enrichment and work engagement is strengthened when academic staff is confronted with high job demands. This study shows that systematic training programs are needed to enhance more supportive supervisory practices. To reduce the adverse impact of colleague support on work engagement, academics should be exposed to how communication content can have profound influence on both emotional and instrumental functions of different sources of support. The management should recruit and develop academics with positive core selfevaluation. Besides, efforts to promote prestige image of the universities is likely to bear fruitful results in enhancing the work engagement. In addition, the management should assist employees in achieving greater balance between their work and personal life through work life policies and programs. Last but not least, the limitations of the present study and some suggestions for future research are discussed as well